2023
DOI: 10.1021/acscatal.2c06412
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Oxygen Vacancies and Ni0 Species to Promote the Stability of a Ni/ZrO2 Catalyst for Dry Reforming of Methane at Low Temperatures

Abstract: Low-temperature dry reforming of methane (DRM) can avoid the sintering of nickel and reduce the cost of the process. However, inefficient activation of CO 2 and oxidization of Ni 0 hamper the catalytic performance of Ni-based catalysts at low temperatures. Herein, a Ni/ZrO 2 catalyst was prepared and used in the DRM reaction, which exhibited stable activity at low temperatures (400, 320 and 300 °C) for 10 h, with CH 4 and CO 2 turnover frequencies of 0.26 and 0.18 s −1 at 320 °C, respectively. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In contrast, the 3Ce-MnO x catalyst displays several oxygen desorption peaks at 250–500 °C and above 600 °C. The peaks in the temperature range of 250–500 °C could be attributable to chemically adsorbed oxygen , and high area ratio of chemisorbed oxygen desorption peaks were also observed on catalysts with different Ce loadings (Figure S7 and Table S3), which may be due to the addition of Ce-induced oxygen vacancies in the catalysts, resulting in a higher surface chemisorbed oxygen content. Two types of adsorption peaks are associated with surface lattice oxygen (red peak) and bulk lattice oxygen (blue peak) above 600 °C, and the former is conducive to C–H bond activation of CH 4 and C 2 product selectivity .…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, the 3Ce-MnO x catalyst displays several oxygen desorption peaks at 250–500 °C and above 600 °C. The peaks in the temperature range of 250–500 °C could be attributable to chemically adsorbed oxygen , and high area ratio of chemisorbed oxygen desorption peaks were also observed on catalysts with different Ce loadings (Figure S7 and Table S3), which may be due to the addition of Ce-induced oxygen vacancies in the catalysts, resulting in a higher surface chemisorbed oxygen content. Two types of adsorption peaks are associated with surface lattice oxygen (red peak) and bulk lattice oxygen (blue peak) above 600 °C, and the former is conducive to C–H bond activation of CH 4 and C 2 product selectivity .…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have shown that the more oxygen vacancies introduced in CeO 2 samples with different Cu contents, the higher the CO 2 adsorption amount and the greater the adsorption capacity of the resulting intermediates, which can lead to excellent C 2 + selectivity under the synergistic effect of Cu 0 and Cu + active sites to promote CÀ C coupling. [28,51,52] In short, with the change in Cu content, the oxygen vacancy content changed, significantly affecting the CO 2 adsorption amount and the adsorption capacity of intermediates on the catalyst surface, resulting in the difference in CO 2 reduction activity in this series of samples. The electrochemical active surface area (ECSA) and electrochemical impedance spectroscopy (EIS) of the catalyst were investigated to reveal the reason for the high catalytic performance of the Cu 9.77 /CeO 2 catalyst in CO 2 RR.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure a,b, the adsorption configuration of CO 2 is somewhat different for these two catalysts. On the Ni/MgO catalyst, CO 2 molecules have been found to adsorb as carbonate and bicarbonate species. , It is observed that the strength of the adsorption peaks gradually decreases with increasing temperature until they practically vanish. Conversely, on the Ni/MgCe 0.12 O x catalyst, CO 2 is primarily observed to adsorb in the bicarbonate configuration, with minimal changes in the observed adsorption peak intensity with increased temperature.…”
Section: Resultsmentioning
confidence: 99%